Germaine de Staël and German Women : Constructing Literary Authority. - Martin, Judith E. (Rowman & Littlefield Pub. Group, 2011)
Germaine de Staël in Germany: Gender and Literary Authority (1800-1850) investigates Staël's significance as an icon of female artistic genius and political engagement for two generations of German women, including Caroline A. Fischer, Caroline Pichler, Johanna Schopenhauer, Bettina von Arnim, Ida Hahn-Hahn, and Luise Mühlbach. These authors drew a significant impetus from Staël's exemplary life and writings, especially her influential novels of political and artistic heroines, Delphine (1802)and Corinne, or Italy (1807), referring to them in order to authorize their own discourses on art and.